A Simple Sperm DNA Toroid Integrity Test and Risk of Miscarriage. (15th January 2015) - Chan, Philip J.; Orzylowska, Eliza M.; Corselli, Johannah U.; Jacobson, John D.; Wei, Albert K.
Abstract : Current methods of analyzing sperm chromatin competency overlook the inner sperm compartment which is inaccessible to probes and reagents. By breaking the molecular protamine disulfide bridges, the DNA toroids are exposed to integrity analysis. The aim was to develop a simple nuclear toroid test and determine its association with fertilization, pregnancy, and miscarriage. The approach involved treating washed sperm remaining after ICSI procedures (N = 35 cases) with acidified Triton X-100 and dithiothreitol (DTT) before Diff-Quik staining. Percentages of sperm with normal chromatin indicated by light-colored nuclei were assessed. The toroid integrity test showed more sperm with normal chromatin in the pregnant group (73.6 ± 1.7%, mean ± SEM) when compared with the miscarriage (51.2 ± 6.6%) or nonpregnant groups (60.9 ± 4.8%). Furthermore, the toroid results were correlated with ICSI fertilization (R = 0.32, P = 0.04 ) and pregnancy outcome (pregnant cases 73.6 ± 1.7% versus nonpregnant 58.0 ± 3.9%, P = 0.001 ). ROC calculated cut-off was >70.0% for normal toroid integrity (sensitivity 0.98, specificity 0.33, and diagnostic accuracy 78.3%). An association between normal sperm toroid integrity and miscarriage was evident when the staining procedure included acidified detergent DTT pretreatment.